Fetomaternal hemorrhage among pregnant women in Accra, Ghana. Issue 3 (4th July 2019) - Akorsu, Elliot E.; Acquaye, Joseph K.; Benneh, Amma A.; Oppong, Samuel A.; Olayemi, Edeghonghon
Abstract: Objective: To determine the occurrence of and risk factors for fetomaternal hemorrhage (FMH) among pregnant women at Korle Bu Teaching Hospital in Accra, Ghana. Methods: A prospective study of FMH among pregnant women without hemoglobinopathies in the second trimester attending prenatal care between October 2015 and May 2016 performed using the Kleihauer‐Betke test. Volume of FMH was estimated; ABO and Rh blood groups of participants were determined. A data extraction form and structured questionnaire were used to collect demographic and clinical information, and data on risk factors. Results: Of 151 participants, 32 (21.2%) had FMH. Almost 18% (n=27) had FMH at baseline (16–24 weeks), 10% (10/100) at 28–32 weeks, and 11.1% (11/99) at 34–37 weeks of pregnancy. Volume of FMH was less than 30 mL in 30 (19.9%) women, whereas it was greater than 30 mL in 2 (1.3%) women. No identifiable patient‐specific factors were associated with occurrence of FMH. Conclusion: FMH is common among pregnant women in Ghana and can occur as early as 16 weeks, without identifiable risk factors. RhD negative women who may be pregnant with RhD positive fetuses should be screened early in pregnancy, not only at delivery, for occurrence of FMH. Abstract : Fetomaternal hemorrhage is common among pregnant women in Ghana, occurring as early as 16 weeks and without identifiable risk factors.